Development and validation of a simulation-based safety evaluation program for a mega floating crane. (October 2017) - Ham, Seung-Ho; Roh, Myung-Il; Lee, Hyewon; Hong, Jin-Wuk; Lee, Hong-Rae
Highlights: We develop a differentiated program that is dedicated to a mega floating crane. The program executes dynamic analysis him- or herself. The program reduces modeling time and effort. The program supports mechanical equipment for more accuracy. Simulation results are validated by comparison with the measurement of real operation. Abstract: The motions of the mega floating crane and the lifted module must be evaluated in advance, to determine whether they satisfy the safety criteria or not. Due to the limitations of the existing dynamic analysis programs, we develop a differentiated program that is dedicated to the mega floating crane. This program is focused on reducing modeling time, while increasing modeling accuracy. Furthermore, it can model the block loader that distributes the tension in wire ropes between the lifted module and the block loader equally, and link beams that are used to connect hooks by hinge joints. The equations of motion based on multibody system dynamics are derived. Wave, wind, and current are included as external environmental loads. A direct volume calculation method below the water plane is adopted to find the buoyant force and center of buoyancy. External loads are verified by commercial program. Finally, the simulation results of the module erection are validated by comparison with the measurement of real operation.